Mean and interact: Education and bilingualism in southern Peru - Godenzzi, Juan Carlos (1993)
The background of this exhibition is the reality of the indigenous rural school in southern Peru, its sociolinguistic context and its main problems. Likewise, it has as a frame of reference the experiences and debates arising from the application of various alternative educational programs or projects. Against this background and framework, I offer some reflections on aspects of bilingual education: the teaching of reading and writing, the teaching of the mother tongue and, finally, the teaching of the second language. My fundamental interest is to make explicit some dimensions whose development seems crucial to achieve a substantial improvement of the indigenous rural school, but also to give a new focus and renew any educational proposal.